Evaluation on the operational effects of U-turn movement - Siti Aisyah, Zakaria (2012)
Nowadays, people always want to move clearly to their destination. Many road and junction were upgraded especially in urban area because of the capacity of vehicles increase from time to time. So, it is important to monitor and analyse the road that can make congestion so that it can be improved by using traffic lights, roundabout, and the change of road geometry and so on. This study is referring to unsignalized junction, that is U-turn located at Batu 6 Federal Route Gambang-Kuantan, Kuantan Pahang near Kem Tentera Udara Malaysia (TUDM). Raff Method is the method used to analysed Utum study area. By using the Raff method, critical gap and follow-up time of other vehicles can be identified study area. Data taken three times during the day in good weather conditions. After the traffic flow data and the U-turn geometry is taken, the data will be analysed using the Raff Method and critical gap at U-turn area is unknown. The results obtained showed that the gap time and time lag is really bad. In this study, the solution to this problem is proposed and one of the proposals is to replace the conventional U-turn with the modern U-turn.